Controlling w globalnym przedsiębiorstwie. Przesłanki i problemy konstruowania i działania - Nowosielski, Stanisław (Controlling in the global business. Premises and problems of constructing and acting, 2008)
The article at first describes basic questions connected with globaiization and next it shows chosen features of global business management. In the further part, it presents causes and some of the problems of controlling in this kind of business. It also describes selected conditions of constructing |&d acting in the controlling's global business. Additionally, it syntetically characterizes, the way to lie integral idea of the controlling. Finally, the article focuses on the controlling of global teams.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 335-343